Damage evaluation and strain monitoring for composite cylinders using tin-coated FBG sensors under low-velocity impacts. (1st June 2015) - Kim, Sang-Woo; Kim, Eun-Ho; Jeong, Min-Soo; Lee, In
Abstract: Background/purpose: The impact-induced damage of composite structures induced by low-velocity impacts were evaluated to verify the damage evaluation concept using the "memory effects" of tin-coated FBG sensors. Methods: Low-velocity impact tests for the composite cylinder with tin-coated FBG sensors were performed at three impact energies. Hoop ring tests for the composite cylinder including impact-induced damage were additionally undertaken in order to measure the burst pressure and to study the parameter correlations. The test results were compared with the numerical results obtained by a finite element analysis (FEA) based on a continuum damage mechanics (CDM) considering damage model. The parameter correlations among the impact parameters and the residual strains induced by tin-coated FBG sensors were investigated based on the tests results. Results: Impact behaviors obtained by the tests and the numerical simulation were agreed well. It was found that tin-coated FBG sensors can monitor the strain of the composite cylinder under low-velocity impacts and their strain monitoring capability is comparable to that of normally used FBG sensors. The residual strains of tin-coated FBG sensors were correlated with the impact parameters such as the impact energy, the sensing position of the sensors, and the burst pressure of the composite cylinder. Conclusion: The correlations among the residual strains and the parameters proved the damage evaluation concept for composite cylinders using the "memory effects" of tin-coated FBG sensors under low-velocity impact conditions; that is, the impact-induced damage, impact location, and burst pressure can be inversely evaluated by referring to the correlations.